2015
DOI: 10.3892/ijo.2015.3313
|View full text |Cite
|
Sign up to set email alerts
|

PP2B and ERK1/2 regulate hyaluronan synthesis of HT168 and WM35 human melanoma cell lines

Abstract: Hyaluronan (HA) is the major glycosaminoglycan component of the extracellular matrix in either normal or malignant tissues and it may affect proliferation, motility and differentiation of various cell types. Three isoforms of plasma membrane-bound hyaluronan synthases (HAS 1, 2 and 3) secrete and simultaneously bind pericellular HA. HAS enzymes are subjects of post-translational protein phosphorylation which is believed to regulate their enzymatic activity. In this study, we investigated the HA homeostasis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…These findings suggest that PACAP has an important function in hyaluronic acid turnover via the activation of hyaluronic acid synthases and regulation of hyaluronan degradation. However, the addition of hyaluronic acid is able to prevent the harmful effects of oxidative stress [42] and induces migration of tumor cells [43], but no clear data can be found in connection with hyaluronan catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that PACAP has an important function in hyaluronic acid turnover via the activation of hyaluronic acid synthases and regulation of hyaluronan degradation. However, the addition of hyaluronic acid is able to prevent the harmful effects of oxidative stress [42] and induces migration of tumor cells [43], but no clear data can be found in connection with hyaluronan catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This disappearance of hyaluronan in tumor tissue correlates with the loss of HAS1 and HAS2, and is associated with increased recurrence of melanoma and short disease-specific survival time (Poukka et al, 2016). Although the tumor tissue is almost hyaluronan negative in melanoma, tumor cells stimulate its synthesis in stromal fibroblasts (Pasonen-Seppänen et al, 2012b;Willenberg et al, 2012) and metastases (Katona et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because very little is known about hyaluronan in melanocytes (Bhavanandan, 1981;Katona et al, 2016), we characterized hyaluronan and the enzymes related to its metabolism, and we explored the contribution of hyaluronan to UVB-induced inflammation in primary melanocytes. The results suggest that hyaluronan and its fragmentation are involved in the inflammatory effects of UVB and melanocyte susceptibility to early melanoma development.…”
Section: Introductionmentioning
confidence: 99%
“…Increased MMP activity was detected in the ECM of cardiac muscle tissue during aging (Meschiari et al 2017), but we showed a PACAP-dependent reduction of MMPs in mechanical overload of chondrogenic cell cultures (Szentleleky et al 2019). RHAMM is an intracellular HA-binding receptor which can be activated by ERK (Katona et al 2016). Its expression is reduced in aged PACAP KO animals, suggesting that intracellular HA function is decreased as it was demonstrated in skin aging (Tzellos et al 2009).…”
Section: Discussionmentioning
confidence: 99%